Distribution of butyltins at dredged material dumping sites around the coast of China and the potential ecological risk. (January 2019) - Wang, Xiaomeng; Kong, Lingna; Cheng, Jiayi; Zhao, Dongmei; Chen, Hong; Sun, Runjun; Yang, Wenchao; Han, Jianbo
Abstract: Previous research has found butyltin pollution at dumping sites, which are the final fate of dredged material mostly originating from harbors and navigation systems. The distribution and impacts of butyltins were assessed in sediments at 12 dumping sites of China. Total butyltins (monobutyltin, dibutyltin, and tributyltin) concentrations ranged from 1.76 to 486.62 ng Sn g −1 dw. This study also presents evidence of considerable historic inputs of tributyltin (TBT) to Dumping sites 01, 05, 06, 08, 09 and 11, with evidence of heavier recent TBT input at Dumping site 04 and 10. The butyltin contamination at dumping sites was comparatively light and historic compared to research in other countries, but was more serious than other sea regions. TBT levels at Dumping site 09 probably have negative effects on biological systems. Overall, more attention should be paid to the level and impacts of butyltins in the sediment at dumping sites in China. Highlights: Levels of butyltins in sediment at dumping sites in China were investigated. The results presented historic TBT source at Dumping site 01, 05, 06, 08, 09, 11. It showed evidence of heavier recent input of TBT at Dumping site 04 and 10. The butyltin levels at dumping sites were higher than other sea regions in China. TBT level at dumping sites probably has negative effects on biology of organisms.